The integrity of election organizers in the 2020 simultaneous regional head elections in Sekadau Regency - Hayatullah, Hengki; Sardini, Nur Hidayat (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2022)
This research objective was to examine the integrity of the election organizers by analyzing the factors that led to the issuance of the Constitutional Court Decision Number: 12/PHP.BUP-XIX/2021 regarding the recount of the 2020 Simultaneous Regional Head elections in Sekadau Regency. It was known that the lawsuit resulting from the recapitulation of votes was filed by the pair Rupinus-Aloysius as the incumbent. The pair received 56,479 votes or 49.2 percent. Meanwhile, the rival pair Aron-Subandrio received 58,023 votes or 50.8 percent. This research used a descriptive qualitative method through a case study approach, which examined a "single instrumental case". Data collection techniques were done through an informant interview (in-depth interview) and document studies. The data was obtained by taking directly from the sources of the General Election Commissions, The General Election Supervisory Agency (Bawaslu), and the Sub-district Election Committees of Sekadau Regency. The research results first showed the organizers' negligence factor during recapitulation by entering Form C. The results of KWK Holograms from 65 Polling Stations (TPS) in the Belitang Hilir Sub-district into one box must remain in the box at each Polling Station. Second, the Sekadau Technical Guidance Factor of General Election Commissions (Bimtek) for Commitment Making Officer was not optimal. The technical guidance focused on using the Recapitulation Information System (Sirekap) for two days. When the process/ stages were carried out without integrity, the election results were also not with integrity, i.e., it is due to the organizers' poor integrity.